2017
DOI: 10.1128/aem.00797-17
|View full text |Cite
|
Sign up to set email alerts
|

Defining Genetic Fitness Determinants and Creating Genomic Resources for an Oral Pathogen

Abstract: Periodontitis is a microbial infection that destroys the structures that support the teeth. Although it is typically a chronic condition, rapidly progressing, aggressive forms are associated with the oral pathogen Aggregatibacter actinomycetemcomitans. One of this bacterium's key virulence traits is its ability to attach to surfaces and form robust biofilms that resist killing by the host and antibiotics. Though much has been learned about A. actinomycetemcomitans since its initial discovery, we lack insight i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(44 citation statements)
references
References 95 publications
3
41
0
Order By: Relevance
“…Genes encoding products related to translation, lipid metabolism, and cell wall biogenesis were enriched among essential genes (COGs J, I, and M) ( Fig. 2 ), consistent with essential genomes identified in other bacterial species ( 23 , 27 ). Genes associated with signal transduction, transcription, general functions, or of unknown function were depleted (COGs K, R, S, and T), suggesting that these functions are less important for growth on blood agar.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Genes encoding products related to translation, lipid metabolism, and cell wall biogenesis were enriched among essential genes (COGs J, I, and M) ( Fig. 2 ), consistent with essential genomes identified in other bacterial species ( 23 , 27 ). Genes associated with signal transduction, transcription, general functions, or of unknown function were depleted (COGs K, R, S, and T), suggesting that these functions are less important for growth on blood agar.…”
Section: Resultssupporting
confidence: 80%
“…Conversely, 100 to 300 noncore genes were estimated previously to differ between any two strains of S. mutans ( 29 ). When comparing the essential genomes of two strains of the same species, differences in essential gene content and metabolic pathways have been reported ( 26 , 27 ). Clearly, accessory gene content is important and could alter gene-gene networks in such a way that genes that are essential in one strain become functionally redundant in another strain.…”
Section: Resultsmentioning
confidence: 99%
“…This ltx gene deletion resulted in a complete lack of attachment in vivo and reduced binding to hydroxyapatite in vitro, resulting from reduced expression of genes in the tad operon [55]. This linkage between ltx genes and flp genes was confirmed in another model, which showed that, when A. actinomycetemcomitans was stressed, four genes were linked: flp, ltx, pgA, and tfox [56].…”
Section: Interventional Studiesmentioning
confidence: 71%
“…In this study, the core genes were identified by comparative genomics and may or may not be the same as essential genes that require experimental confirmation. A previous study utilizing rapid transposon mutant sequencing (Tn-Seq) had established the presence of essential genomes in two divergent A. actinomycetemcomitans strains, VT1169 and 624 strains [24]. Notably, 307 of the 319 essential genes matched to our core gene pool.…”
Section: Discussionmentioning
confidence: 96%
“…To determine pathways affected by the differentially expressed genes, we used the KEGG Mapper Search and Color Pathway tool as previously described [24,49] using the locus tag of each differentially expressed genes obtained from each media. A comparison of the pathways affected were then attempted.…”
Section: Metabolic Networkmentioning
confidence: 99%